Acts of Last Resort: Asylum, Whistleblowing and the Anthropology of Secrecy. Issue 2 (15th March 2018) - Reid, Alison; Skuse, Andrew
Abstract : Anthropologists face fresh challenges as they endeavour to conduct research in an increasingly securitised and secretive world. Those who wield asymmetrical power in society often seek to guard information and knowledge. Therefore, it is imperative that anthropologists seek new ways of navigating the politics of secrecy if they are to reveal anything of its inner workings. In pursuit of this imperative, this paper examines practices of whistleblowing and posits secrecy as a dialectic that is characterised by processes and practices that work towards concealment, as well as revelation. In shifting the analytical focus from that which is concealed to what is revealed in acts such as whistleblowing, we contend that anthropologists may elucidate something about secrecy that is revealing of context-specific forms of agency and power. In doing so, analysis draws upon Australia's secretive immigration and border protection regime and in particular a recent government inquiry that enabled whistleblowers to reveal details of secrets that had previously been closely held.